The Superiority in Christian Grey in The Fifty Shades Trilogy by EL James - Reswa, Dewi Maharani Indah; Nurochman, Nurochman; Setiarini, Ni Luh Putu (Journal of Language and Literature, 2016)
In Superiority is a constant effort to be better, to approach the purpose of what people want to achieve. People try hard not to be better, but to control. This study is aimed to find (1) the characters of Christian Grey, (2) the forms of expression of superiority from Christian Grey, and (3) the factors that influence the appearances of the superiority in Christian Grey. The researcher uses descriptive qualitative method in conducting the research. The sources of the data are taken from Fifty Shades trilogy. The researcher collects the data by reading the Fifty Shades trilogy one by one,marks down the dialogue and line in the novel, classifying the data that shows (1) the characters of Christian Grey, (2) the forms of expression of superiority from Christian Grey, and (3) the factors that influence the appearances of the superiority in Christian Grey, and makes sure that the finding is exactly right to answer the problem formulatio by referring back to the theory itself. The researcher found data that can answer the three of problem formulation. The first finding is the characters in Christian Grey. There are 12 characters that was found by the researcher in Christian Grey, they are self-confident, arrogant, bossy, romantic, caring, mysterious, selfish, generous, control freak, hotheaded, stubborn and kind-hearted. The second finding is such as Self-Confident, Arrogant, Bossy, Romantic, Caring, Mysterious, Selfish, Generous, Control Freak, Hotheaded, Stubborn and Kind-Hearted. The second  finding is the form of expression of superiority from Christian Grey that can be seen in three forms, that are: Attitude, Thoughts, and Face Expression. The last finding, the researcher found the factors that influence the superiority in Christian Grey are: Dark Past Time. In the dark past time, the writer divided into three parts, such as: Tormented, Sexual Violence, and Poorness, (2) Succesful, (3) Wealth, (4) Power.Keywords: Superiority, Character, Characteristic